Effect of sowing date on the behavior of two genotypes of sunflower. I. Phenological and agronomical aspects - Campbell, Atys Tenfuss; Athayde, Manoel L. F. (Pesquisa Agropecuaria Brasileira, 2014)
The present experiment was conducted in Jaboticabal, SP, Brazil, with the objetive of evaluating the behavior of two genotypes of sunflower (Helianthus annuus L.) with respect to production of dry matter, and agronomic characteristics. The plan used was randomized blocks with four replications, and the treatment was composed of five sowing dates: January 20, February 20, March 5, March 20, April 5, with the hybrid Contissol 812 and the cultivar IAC-Anhandy, with 80 cm between rows and five plants per linear meter. The delay in the sowing date exercised a significant depressive effect on the production and distribution of dry matter kg/ha in the stem, leaves, head, and in the total, and also reduced significantly the number of days to the initiation of flowering, plant height, number of leaves, the diameter of the head and of the basal region of the stem. The production of grains was: 2,942, 2,005, 1,243, 1,073 and 809 kg/ha, as means in the two genotypes. It is concluded that the two genotypes studied behaved in the same way and that the sowings realized until the end of February were the best; for those realized later, the growth and development of the plants were affected negatively, resulting in undesirable levels of achene production.
Keywords: dry matter; achene production; Helianthus annuus